Use of energy drinks by male students of Qassim University, Saudi Arabia - Alrasheedi, Ahmad A.; Mozah, Ali A. Bu; Alharbi, Omar H.; Alghadouni, Saleh A.; Alfreedy, Mohammad S.; Alfawzan, Abdullah I. (International Journal Of Community Medicine And Public Health, 2017)
Background: Estimate the rate of consuming energy drinks among male students of Qassim University and to evaluate the pattern, knowledge and behavior of energy drinks among them. Methods: This cross sectional study was conducted among students of Qassim University during December 2014 and January 2015. Data were collected using a self-administered questionnaire. Results: This study showed that 37.8% of participants reported consuming energy drinks. With regard to the colleges, the students of collage of sciences had significantly the highest range of consuming energy drinks. Only a small proportion have knowledge about energy drinks regarding their effects, advantages, ingredients and adverse effects. The most common reasons to consume these drinks were habitation followed by being to imitate friends. Conclusion: Consumption of energy drinks among male students at Qassim University are found to be approximately 37.8% which almost near to what have been seen in some studies. Educational programs should be designed and implemented at all levels of schools and at the community level to raise the level of awareness of health effects of theses drinks.